Walter Liese, 1926-2023 - Čufar, Katarina (Les (Ljubljana), 2023)
Prof. Dr. Dr. h. c. mult. Walter Liese (1926-2023) was a leading scientist, teacher, mentor, director, leader, president of IUFRO, multiple honorary doctor and ambassador of science in the forestry and wood science community. After his BSc and PhD in forestry he pioneered and carried out outstanding work in the field of electron microscopy and the biology and protection of wood and bamboo. From 1963 to 1991, he was a professor at the University of Hamburg and director of its Institute of Wood Biology and Wood Protection, and a Director of the Federal Research Centre for Forestry and Forest Products in Hamburg, Germany. His work had a decisive influence on the development of science, and the laboratories he led were a reference point for wood and bamboo science worldwide. He was an active member of IUFRO and its president from 1977 to 1981, where he acted as an outstanding ambassador and mediator for science. He supported the scientific community in Slovenia. In 1994, he was awarded an honorary doctorate by the University of Ljubljana. Even after his official retirement, he continued his outstanding work, remained committed to science and connected to his worldwide scientific community.
Keywords: bamboo; bambus; biologija lesa; electron microscopy; elektronska mikroskopija; IUFRO; Liese, Walter; wood biology; wood preservation; zaščita lesa